Diversity of bathyal macrofauna on the northeastern Pacific margin: the influence of methane seeps and oxygen minimum zones - Levin, L A; Mendoza, G F; Gonzalez, J P; Thurber, A R; Cordes, E E (Marine Ecology, 2010)
The upper continental slope in the northeastern Pacific Ocean is intercepted by a deep oxygen minimum zone (OMZ; 650–1100 m) and punctuated by conduits of methane seepage. We examined the effects of these two dominant sources of heterogeneity on the density, composition and diversity of heterotrophic macrofauna off Hydrate Ridge, Oregon (OR; 800 m water depth), where the seeps co-occur within an OMZ, and off the Eel River, Northern California (CA; 500 m), where seeps are overlain by better oxygenated waters. We hypothesized that seeps (containing clam beds and microbial mats) should contribute a suite of distinct species to the regional margin species pool but that OMZ-associated hypoxia would dampen seep-related heterogeneity. Macrofaunal densities were highest (23,000–33,510 ind·m−2) in the CA seep sediments and in the OR near-seep samples, intermediate in the OR seep, CA near seep and CA and OR 500-m margin sediments (10,054–19,777 ind·m−2), and lowest in the CA and OR OMZ habitats at 800 m (4269–7847 ind·m−2). Annelids constituted over 50{%} of the taxa in all but the CA clam bed and OR microbial mat sediments, where mollusks were abundant. Approximately 50{%} of seep species appeared to be habitat endemic; species present in microbial mats largely formed a subset of those present in the clam beds. Dorvilleid and ampharetid polychaetes were dominant in the seep sediments; non-seep margin sediments at 500 and 800 m were populated heavily by branchiate polychaetes including cossurids and paraonids. Alpha diversity (Es[20] calculated per core) was lowest and rank 1 dominance was highest in the CA and OR microbial mat habitats. Pooled analyses of Es[100] revealed highest species richness in the CA clam bed and near-seep habitats (30.3 and 29.6, respectively), and lowest species richness in the OR microbial mat and near-seep habitats (16.5 and 17.9, respectively). Non-seep sediments (500 and 800 m) off both CA and OR were more homogeneous (55–57{%} within-habitat similarity) than clam bed and microbial mat sediments (only 32–37{%} within-habitat similarity). CA sediment macrofauna generally exhibit higher alpha diversity, and as habitats are combined, a higher rate of increase in the slope of the species accumulation curves than do OR margin macrofauna. Methane seeps in the NE Pacific introduce significant heterogeneity that increases margin biodiversity at multiple spatial scales. However, our hypothesis that the OMZ would lessen the seep contributions to diversity was not supported. The better oxygenated CA seeps at 500 m shared more of the background margin fauna (at 500 m) than did the OR seeps at 800 m (with OMZ fauna at 800 m). Geographical differences in the fluxes of methane-rich fluids and the increased reliance on chemosynthetic food sources with increased depth could explain these results.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)